2011
DOI: 10.1073/pnas.1012645108
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and aging-dependent development of arthritis in NADPH oxidase 2 deficiency through altered differentiation of CD11b+ and Th/Treg cells

Abstract: Emerging evidence indicates that NADPH oxidase (NOX) and its reactive oxygen species (ROS) products modulate a variety of cellular events, including proliferation, differentiation, and apoptosis. In this study, we investigated the functions of NOX2 and ROS in immune modulation using NOX2 knockout (KO) mice. Interestingly, NOX2 KO mice spontaneously developed arthritis with onset at 6-7 wk of age and high incidence (60%) at 15-18 wk of age. Arthritis severity in NOX2 KO mice was proportionally increased with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
97
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 35 publications
11
97
2
1
Order By: Relevance
“…However, literature reports suggest that a reduction in ROS levels and signaling may also be detrimental (5,6). For example, in the musculoskeletal system, decreased ROS concentrations have been shown to promote inflammation (6).…”
mentioning
confidence: 99%
“…However, literature reports suggest that a reduction in ROS levels and signaling may also be detrimental (5,6). For example, in the musculoskeletal system, decreased ROS concentrations have been shown to promote inflammation (6).…”
mentioning
confidence: 99%
“…These cells -depending on current ROS tissue status and expression of one of the regulatory moleculesmay differentiate in two directions: FoxP3 + Tregs (in the case of IDO expression) or TH17 (in the case of HIF-1α expression), where an advantage of differentiation in one direction results in the simultaneous inhibition of differentiation in the opposite direction [14,54,55,58,59]. These are important observations, considering the studies conducted by Faleo et al, who found that FoxP3 + Tregs may be involved in the mechanism of preventive effect of HBOT in an animal model (NOD mice) of autoimmune diabetes [21].…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…ROS have been shown to regulate autoimmune responses. Impairment of Nox2-dependent ROS generation in neutrophil cytosolic factor 1 (Ncf1)-mutated mice results in enhanced disease severity in several different animal models of arthritis [11,18,19]. Macrophage-restricted expression of functional Ncf1 restored arthritis resistance in a CIA model but not in a T cell-independent anti-collagen antibody-induced arthritis model.…”
Section: ) Signaling Role In T Cell Tolerancementioning
confidence: 99%
“…In addition, activation of naïve T cells from Nox2-deficient mice exhibited a skewed Th17 phenotype [19]. The immediate-early response gene X-1 (IEX-1, also known as IER3) is involved in preventing the production of ROS in mitochondria.…”
Section: ) Regulation Of T Cell Differentiationmentioning
confidence: 99%
See 1 more Smart Citation